Graduation in Accounting Sciences - Emphasis on Competences: Contributions to the Debate - Laffin, Marcos (Education Policy Analysis Archives, 2015)
The productive restructuring required new training bases to ensure improvements in the professional performance. The undergrad degree in Accounting in Brazil, through the curriculum guidelines of the course, adopted the training path based on competences and skills. This tension inclined to competences required a training to respond to the labor market, depriving the understanding of accounting conceptual dimension at the expense of its technical rationality. In this context, the goal of this study is to discuss limitations of pedagogical competences regarding contradictions between the demand of an accounting professional who conciliates accounting knowledge and participate in social development through its professional performance. Considering its bibliographical and documentary nature, this study sought contributions from Ramos (2001), Mendez (2011), and Kuenzer (2007) to support its analysis of the perspective in the Resolution CNE/CES nº 10/2004, which established guidelines to the undergrad degree in Accounting. It was concluded that the reification of Accounting curriculum by competences, which is subject by the exam of sufficiency, does not contribute to a full professional development, which would allowed the exercise of professional and citizenship autonomy, contrarily, it imposes limits to the development of the accounting knowledge.